Arterial stiffening and systemic endothelial activation induced by smoking: The role of COX-1 and COX-2. (15th June 2015) - Vlachopoulos, Charalambos; Aznaouridis, Konstantinos; Bratsas, Athanassios; Ioakeimidis, Nikolaos; Dima, Ioanna; Xaplanteris, Panagiotis; Stefanadis, Christodoulos; Tousoulis, Dimitris
Abstract: Background: Arterial stiffness is an established predictor of cardiovascular risk. We explored the effects of acute smoking on arterial stiffness, systemic inflammation and endothelial activation in chronic smokers and the contribution of cyclooxygenases-1 and 2 (COX-1 and COX-2). Methods and results: In a randomized, double-blind, cross-over study, we investigated in 28 young smokers the vascular and systemic effects of smoking one cigarette, 3 h after receiving 1000 mg of aspirin (a non-selective COX-1 and COX-2 inhibitor) or placebo (aspirin substudy), or 200 mg of celecoxib (a selective COX-2 inhibitor) or placebo (celecoxib substudy). Smoking increased carotid–femoral pulse wave velocity (PWV, a marker of aortic stiffness), indicating an adverse effect on arterial elastic properties. Similarly, circulating levels of asymmetric dimethylarginine (ADMA) were increased after smoking. Aspirin fully prevented the smoking-induced increase of PWV after smoking. In contrast, celecoxib only partially prevented the smoking-induced increase of PWV. Both aspirin and celecoxib prevented to a similar extent the increase of ADMA levels after smoking. Conclusions: Smoking one cigarette is associated with a deterioration of arterial stiffness and with systemic endothelial activation in chronic smokers. Both COX-1 and COX-2, but primarily COX-1, mediate these unfavorable effects of smoking.